Training on the Implementation of the Independent Curriculum (IKM) for Teachers at Roudlotul Ulum Elementary School, Bangil, Pasuruan - Nuril Nuzulia; Novia Solichah (Journal of Community Service and Empowerment, 2025)
Roudlotul Ulum Bangil Pasuruan Elementary School began implementing the Independent Curriculum (Kurikulum Merdeka) in the 2022/2023 academic year for grades 1 and 4. The school chose the Independent Sharing (Merdeka Berbagi) model, developing its own curriculum tools. However, most of the training attended by teachers was conducted online, limiting their practical understanding, particularly in designing teaching modules and assessment instruments aligned with the new curriculum. This community service program aims to strengthen teachers’ understanding and competence in implementing the Independent Curriculum through a three-stage process: preparation, seminar and training, and follow-up. It involved 28 teachers and was conducted over two days, from 30 to 31 July 2024. The effectiveness of the program was evaluated through pre- and post-training questionnaires and participant reflections. Results indicated a marked improvement in teachers’ understanding and confidence in preparing learning modules and assessment tools aligned with the Independent Curriculum principles. In conclusion, the program achieved its intended objectives. The active participation, institutional support, and demonstrated improvements in teacher competence reflect the relevance and impact of this initiative. The activity also supports Sustainable Development Goal 4 by promoting inclusive and equitable quality education through strengthened teacher capacity.